NON-SKELETON BUILDING OF MULTIPURPOSE DESTINATION - Першаков, В.М.; Луценко, О.К.; Петрова, Т.О.; Соловйов, О.С. (Proceedings of National Aviation University, 2012)
The non-skeleton structure of multipurpose destination is developed from typical reinforce-concrete slabs and intended for building of objects of agroindustrial complex. Fixed building is under the test loadings. After researches was established, that a construction has sufficient bearing capacity. Non-skeleton building is urgent for storage of agricultural production and storage of eguipment, placing of markets and sport complexes.